Selection and perceived impact of walk-up songs in college baseball - Stokowski, Sarah; Corr, Chris; Godfrey, Michael; Eric, Matthew; Hughes, Chase; Hughes, Rob; Marchal, Matthew; Roby, Taylor (Frontiers in Psychology, 2025)
IntroductionMusic and song have the ability to positively affect athletic performance. Music has been demonstrated to increase physical capabilities and improve cognitive function among both recreational and competitive athletes. This study sought to explore the role of music on athletic performance by examining walk-up songs in competitive athletics.MethodsA sample of 10 participants currently competing in National Collegiate Athletic Association Division I major conference baseball agreed to participate in semi-structured qualitative interviews. Participants were asked to detail the process leading to their selection of a walk-up song and describe the perceived impact of walk-up songs on their athletic performance.FindingsParticipants categorized three salient factors contributing to the selection of their walk-up songs: (1) personal preference, (2) crowd engagement, and (3) song popularity/relevance. In addition, participants indicated that they derived athletic performance benefits from their walk-up song selection based on the ability of a selected song to engage the crowd and narrow their focus prior to an at-bat.DiscussionAlthough participants indicated they selected their walk-up songs based primarily on personal preference, factors pertaining to the desires of participants to engage and appeal to the crowd undoubtedly impacted their walk-up song selection. In this sense, participants indicated the primary benefit derived from walk-up songs was in engaging the crowd in the game itself. Such finding is in contrast to extant scholarship identifying the role of music and song in individual athletic performance and perhaps indicative of the increased role fans occupy in athletic performance.